Think of the Early Career Researchers! Saving the Oceans Through Collaborations - Cosentino, Mel; Souviron-Priego, Lucrecia (Frontiers in Marine Science, 2021)
Oceans are complex systems and problems preventing a sustainable future require complex solutions. This can be achieved through innovative blends of natural and social sciences, with input from stakeholders. There is growing expectation that early career researchers (ECR), especially conservationists, should be more than natural scientists. ECR are expected to have skills in several domains, not all important to the quality of their work. Scientific skills range from knowledge of complex statistics to programming, and experience in different scientific fields. It is not only impossible to master all such tasks in a lifetime, much less as an ECR, but most importantly, attempting to do so means an ECR cannot master any single skill. This is especially true for minorities, non-native English speakers, and those who must juggle doing science with little or no funding, while having other jobs and family commitments. ECR are also expected to participate in activities that, while important for conservation, do not necessarily improve their scientific skills. These are social skills and range from policy engagement to science communication. This can contribute to developing mental health issues as it hinders having a healthy work-life balance. This expectation of engaging in extracurricular activities can overwhelm people with social anxiety and other difficulties with social interactions (e.g., people in the autism spectrum). Through collaborations, we can effectively draw on the more specialised skills of various people. Building an inclusive scientific community for ECR, therefore, calls for seeing diversity of skills, thoughts, and personality traits as its strength.